Single-Lung Transplant Results in Position Dependent Changes in Regional Ventilation: An Observational Case Series Using Electrical Impedance Tomography - Kollengode Ramanathan; Hend Mohammed; Peter Hopkins; Amanda Corley; Lawrence Caruana; Kimble Dunster; Adrian G. Barnett; John F. Fraser (Canadian Respiratory Journal)
Background. Lung transplantation is the optimal treatment for end stage lung disease. Donor shortage necessitates single-lung transplants (SLT), yet minimal data exists regarding regional ventilation in diseased versus transplanted lung measured by Electrical Impedance Tomography (EIT). Method. We aimed to determine regional ventilation in six SLT outpatients using EIT. We assessed end expiratory volume and tidal volumes. End expiratory lung impedance (EELI) and Global Tidal Variation of Impedance were assessed in supine, right lateral, left lateral, sitting, and standing positions in transplanted and diseased lungs. A mixed model with random intercept per subject was used for statistical analysis. Results. EELI was significantly altered between diseased and transplanted lungs whilst lying on right and left side. One patient demonstrated pendelluft between lungs and was therefore excluded for further comparison of tidal variation. Tidal variation was significantly higher in the transplanted lung for the remaining five patients in all positions, except when lying on the right side. Conclusion. Ventilation to transplanted lung is better than diseased lung, especially in lateral positions. Positioning in patients with active unilateral lung pathologies will be implicated. This is the first study demonstrating changes in regional ventilation, associated with changes of position between transplanted and diseased lung.